Asuhan Keperawatan Pada Klien Dengan Post Remove Of Inplate Fraktur Tibia Di RSUD Sukoharjo - Prabowo, Apri Adhi Aji, Okti Sri Purwanti, S.Kep., M.Kep., Ns., Sp.Kep.M.B (2015)
Background : Post Remove of Inplate (ROI) fractures of the tibia are circumstances where it has performed surgery release plate and screws were used to fix the broken tibia . Objective: To determine the nursing care to clients with post ROI tibia fracture include assessment , intervention , implementation and evaluation of nursing . Results :after the nursing care for 3 x 24 hours is obtained , complaints of pain in the client decreased from 6 to 2 , the absence of signs of infection , the patient 's basic needs are met . Conclusion In the nursing diagnoses : acute pain and risk of infection after an evaluation issue is resolved , while the barriers to physical mobility diagnosis problem is resolved in part , to the need for good cooperation between health professionals with clients so that problems can be solved entirely .